Metaphors in the Narrative of Ephesians 2:11-22 : Motion towards Maximal Proximity and Higher Status - Jiménez, Oscar E., (Linguistic Biblical Studies ;, 2022)
Oscar E. Jiménez opens up the multi-dimensional implications of Ephesians 2:11-22 for narrative and theological analysis, demonstrating that each metaphor in the text blends and creates a single, complex narrative. Concentric spatial places construct the text's landscape on which the Gentiles move, each place representing increasing intimacy and familiarity through national, familial, architectural, and cultic images. Christ is the vehicle of that motion, and also the agent, breaking down walls and abolishing enmity, and ultimately building the structure as both builder and cornerstone. This will be an important book for New Testament scholars and scholars interested in the use of linguistics in Biblical studies, in particular literary and narrative analysis to the New Testament epistles.